Error Estimates for a Combined Finite Volume-Finite Element Method for Nonlinear Convection-Diffusion Problems - Feistauer, Miloslav; Felcman, Jiri; Maria Lukacova-Medvid'Ova; Warnecke, Gerald (SIAM journal on numerical analysis, 1999)
The subject of this paper is the analysis of error estimates of the combined finite volume-finite element (FV-FE) method for the numerical solution of a scalar nonlinear conservation law equation with a diffusion term. Nonlinear convective terms are approximated with the aid of a monotone finite volume scheme considered over the finite volume mesh dual to a triangular grid, whereas the diffusion term is discretized by piecewise linear conforming triangular finite elements. Under the assumption that the exact solution possesses some regularity properties and the triangulations are of a weakly acute type, with the aid of the discrete maximum principle and a priori estimates, error estimates of the method are proved.